New approach to generating of human monoclonal antibodies specific to the proteolytic domain of botulinum neurotoxin A - Marina Vladimirovna Silkina; Alena Sergeevna Kartseva; Alena Konstantinovna Riabko; Mariia Aleksandrovna Makarova; Metkhun Madibronovich Rogozin; Yana Olegovna Romanenko; Igor Georgievich Shemyakin; Ivan Alekseevich Dyatlov; Victoria Valerievna Firstova (BioImpacts)
Introduction: Botulinum neurotoxins (BoNTs) cause botulism and are the most potent natural toxins known. Immunotherapy with neutralizing monoclonal antibodies (MAbs) is considered to be the most effective immediate response to BoNT exposure. Hybridoma technology remains the preferred method for producing MAbs with naturally paired immunoglobulin genes and with preserved innate functions of immune cells. The affinity-matured human antibody repertoire may be ideal as a source for antibody therapeutics against BoNTs. In an effort to develop novel BoNT type A (BoNT/A) immunotherapeutics, sorted by flow cytometry plasmablasts and activated memory B cells from a donor repeatedly injected with BoNT/A for aesthetic botulinum therapy could be used due to obtain hybridomas producing native antibodies. Methods: Plasmablasts and activated memory B-cells were isolated from whole blood collected 7 days after BoNT/A injection and sorted by flow cytometry. The sorted cells were then electrofused with the K6H6/B5 cell line, resulting in a producer of native human monoclonal antibodies (huMAbs). The 3 antibodies obtained were then purified by affinity chromatography, analyzed for binding by Western blot assay and neutralization by FRET assay. Results: We have succeeded in creating 3 hybridomas that secrete huMAbs specific to native BoNT/A and the proteolytic domain (LC) of BoNT/A. The 1B9 antibody also directly inhibited BoNT/A catalytic activity in vitro. Conclusion: The use activated plasmablasts and memory B-cells isolated at the peak of the immune response (at day 7 of immunogenesis) that have not yet completed the terminal stage of differentiation but have undergone somatic hypermutation for hybridization allows us to obtain specific huMAbs even when the immune response of the donor is weak (with low levels of specific antibodies and specific B-cells in blood). A BoNT/A LC-specific antibody is capable of effectively inhibiting BoNT/A by mechanisms not previously associated with antibodies that neutralize BoNT. Antibodies specific to BoNT LC can be valuable components of a mixture of antibodies against BoNT exposure.